A Qualitative Comparative Analysis Approach to Sales Strategies and Business Resilience in the Subsidized Housing Sector - Sulati (Journal of Applied Management and Business, 2026)
Aims -  This study aims to identify the combination of various conditions determining the success of subsidised housing sales and to provide evidence-based strategic guidance for developers within the Indonesian property sector. Methodology - The research employs Qualitative Comparative Analysis (QCA) with both crisp-set and fuzzy-set approaches to unravel multivariate interactions between variables simultaneously. Data were obtained from developer sales records for the 2021–2024 period, encompassing house types, pricing, plot locations, and promotional strategies. Findings - The results indicate that subsidised houses in strategic locations achieve high success rates even with price variations or a lack of promotion. Conversely, regular houses only succeed when price, location, and promotion are optimally aligned. These causal configurations confirm that sales success is not the result of a single variable, but rather the complex interaction of multiple factors. Research Limitations/Implications - The study is limited by its case-study focus; thus, further research across different developers and regions is encouraged to strengthen generalisability. Practically, the findings imply that developers must adopt a strategic approach based on combinations of conditions for block allocation, pricing, and promotional planning to enhance revenue evaluation and marketing effectiveness. Originality - This study offers unique value by applying the QCA method to the Indonesian subsidised housing market, moving beyond traditional linear analysis to reveal the holistic configurational causality essential for strategic marketing and accounting management.